PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, SARANA PRASARANA, DAN KOMITMEN GURU TERHADAP KINERJA GURU SMP NEGERI SUBRAYON 02 KABUPATEN KEBUMEN TAHUN PELAJARAN 2013/2014 (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This study aims to analyze: (1) to understand the effect of principal leadership, infrastructure and teachers’ commitment together with teachers’ performance on the performance of teachers’, (2) understanding the effect of principal leadership on knowing teachers’, (3) to know the effect of infrastructure on the teachers’ performance, (4) knowing the effect of teachers’ commitment the teachers’ performanceThe research was held at the Junior High Schools in rayon 2nd Kebumen regency. The study population was a public Junior High Schools in rayon 2nd Kebumen regency there were 184 teachers. The sampling technique which using is proportionale random samples. Techniques of data collection using questionnaires. Analysis using Multiple Regression Analysis and Parcial Correlation.Based on the results of this study can be concluded: (1) there is a positive effect of principal leadership, infrastructure and commitment of teachers’ together with the teachers’ performance. It can be explained that principal leadership, infrastructure and commitment of teachers’ develop so the teachers’ performance increase, (2) there is a positive effect of the principal leadership on the teachers’ performance. It can be explained that principal leadership develop so the teachers’ performance increase, (3) there is a positive effect of infrastructure on the teachers’ performance in public. It can be explained that infrastructure develop so the teachers’ performance increase, (4) there is a positive effect of commitment of teachers on the teachers’ performance. It can be explained that commitment of teachers develop so the teachers’ performance increase.